2013
DOI: 10.5978/islsm.13-or-18
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results of pinpoint plantar long-wavelength infrared light irradiation on blood glucose, insulin and stress hormones in patients with type 2 diabetes mellitus

Abstract: Background and aims: This study was aimed at the development of a novel noninvasive treatment system, "pinpoint plantar long-wavelength infrared light irradiation (PP-LILI)", which may be able to relieve mental stress and normalize blood glucose level via the reduction of stress hormones in type 2 (non-insulin-dependent) diabetes mellitus (DM) patients. Materials (Subjects) and methods: Based on this hypothesis, the present study was undertaken to examine effects of PP-LILI on stress hormones (ACTH and cortiso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Ryotokuji et al indicated that four weeks of FIR radiation administered to the feet of type 2 DM patients significantly reduced cortisol levels and blood glucose levels. 47 Therefore, assuming that FIR therapy normalizes blood glucose levels by reducing serum levels of cortisol (adrenal glucocorticoid hormones) and thereby improves the ability to respond to insulin action in patients with type 2 DM is reasonable.…”
Section: Effects Of Fir On Dmmentioning
confidence: 99%
“…Ryotokuji et al indicated that four weeks of FIR radiation administered to the feet of type 2 DM patients significantly reduced cortisol levels and blood glucose levels. 47 Therefore, assuming that FIR therapy normalizes blood glucose levels by reducing serum levels of cortisol (adrenal glucocorticoid hormones) and thereby improves the ability to respond to insulin action in patients with type 2 DM is reasonable.…”
Section: Effects Of Fir On Dmmentioning
confidence: 99%
“…Our previous study showed that pinpoint plantar longwavelength infrared light irradiation (PP-LILI) stimuli normalizes blood flow and pressure, suppresses ACTH and cortisol levels and improves type II diabetes [1][2][3] . All these evidences suggested that PP-LILI stimuli affect systemic homeostasis and thus it was thought that the stimuli also affect immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that far-infrared radiation therapy to the feet of type 2 DM patients significantly reduced cortisol and blood glucose levels. 15 Far-infrared radiation has generally been evaluated as an effective, safe, and nonpharmacologic alternative for pain relief. Farinfrared rays can induce both thermal and nonthermal effects at the molecular level to influence the health of a whole living organism.…”
Section: Introductionmentioning
confidence: 99%